2019
DOI: 10.1001/jamanetworkopen.2019.14745
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics of Participants in Rheumatoid Arthritis Randomized Clinical Trials

Abstract: This systematic review examines the representation in rheumatoid arthritis randomized clinical trials of racial/ethnic minority groups compared with the representation of these populations in the United States and the representation of women and elderly people with the prevalence of rheumatoid arthritis among these groups nationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 29 publications
(71 reference statements)
3
40
2
Order By: Relevance
“…Nonwhite groups comprise approximately 40% of the US population [22], but represented only 13.4% of all NP participants in studies with ≥1 US-based site. Systematic reviews assessing the racial/ethnic composition of clinical trials on cancer [23], rheumatoid arthritis [24], Alzheimer’s disease [25], and cardiovascular disease [26] have also shown underrepresentation of racial/ethnic minority groups. In a recent systematic review examining the racial/ethnic composition of RCTs on various skin diseases, psoriasis studies were least diverse, with 84.3% of subjects being white [21].…”
Section: Discussionmentioning
confidence: 99%
“…Nonwhite groups comprise approximately 40% of the US population [22], but represented only 13.4% of all NP participants in studies with ≥1 US-based site. Systematic reviews assessing the racial/ethnic composition of clinical trials on cancer [23], rheumatoid arthritis [24], Alzheimer’s disease [25], and cardiovascular disease [26] have also shown underrepresentation of racial/ethnic minority groups. In a recent systematic review examining the racial/ethnic composition of RCTs on various skin diseases, psoriasis studies were least diverse, with 84.3% of subjects being white [21].…”
Section: Discussionmentioning
confidence: 99%
“…This population of patients may limit extrapolation of the results to other ethnicities or patients outside of Mexico and Latin America. A recent systematic review found that out of 126 randomized clinical trials for RA, only 4.4% included Hispanic subjects; therefore, it is not clear whether the results would have been similar if the study were conducted in a more diverse population of patients with RA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethnicity associated with remission at three months, which is consistent with findings from observational studies in the United States where non-white participants were less likely to achieve remission [ 24 ]. There is under-representation of ethnic minorities in RCTs, and the evidence base for therapies may not be valid for some ethnic groups [ 25 ]. It is crucial that RCT sample demographics reflect target populations so there can be confidence in the external validity of the findings to clinical practice in areas serving heterogeneous populations.…”
Section: Discussionmentioning
confidence: 99%